Evaluating the association of childhood sexual abuse with the development of irritable bowel syndrome later in life - a systematic review - Muhammad Umer Junaid,; Asad Saulat Fatimi,; Hareem Rauf,; Muhammad Taha Nasim,; Jawed, Kinza; Kishwar Enam, (Journal of the Pakistan Medical Association, 2024)
Objective: To review available medical literature to elucidate the association between childhood sexual abuse and the development of irritable bowel syndrome later in life. Method: This systematic review was conducted from January to August 2022 and comprised a literature search on Medline, PubMed, Scopus, Embase, Web of Science, and Google Scholar databases for relevant studies published between 2001 and 2021. The Newcastle-Ottawa scale was used to determine the quality of the studies. Data on the prevalence of irritable bowel syndrome were meta-analysed using a Mantel-Haenszel random-effects model in RevMan 5.4.1. Results: Of the 7 observational studies analyzed in detail, 5 (71.4%) had a case-control design, and 2 (28.6%) were cross-sectional studies. Overall, there were 3156 subjects. The prevalence of irritable bowel syndrome in the childhood sexual abuse group was 51.86% (334/644), while it was 36.74% (923/2512) in the non-childhood sexual abuse group. The pooled odds ratio, indicating the association between childhood sexual abuse and irritable bowel syndrome, was 1.87 (95% confidence interval: 1.56-2.26). The study quality was rated as good in 3 (42.8%) cases, fair in 3 (42.8%), and poor in 1 (14.3%). Conclusion: Childhood sexual abuse was found to be significantly associated with the development of irritable bowel syndrome later in life, further strengthening the argument that childhood sexual abuse can lead to long-term detriments extending into adulthood. However, there was no existing literature found that stratified other aspects of irritable bowel syndrome, including symptom severity and childhood sexual abuse being the exclusive cause of irritable bowel syndrome.